Multiple myeloma with isolated central nervous system relapse after autologous stem cell transplantation: A case report and review of the literature - Li, Xian; Wang, Weiqin; Zhang, Xiaohong; Liang, Yun (Frontiers in Oncology, 2022)
Patients with multiple myeloma (MM) rarely present with central nervous system (CNS) involvement as a manifestation of extramedullary disease (EMD), a condition that is associated with poor prognosis. CNS relapse without evidence of systemic involvement is even rarer, and there is no standardized treatment because there are only few case reports. We present a 47-year-old female who was diagnosed with nonsecretory multiple myeloma (NSMM) 9 years previously. She had a complete remission after receiving aggressive therapies, including high-dose chemotherapy and autologous stem cell transplantation (ASCT). However, after 7 years of progression-free survival, she had CNS relapse without evidence of systemic involvement. We switched to a salvage regimen consisting of high-dose methotrexate with lenalidomide. She achieved rapid clinical improvement, with a reduction in cerebrospinal fluid plasmacytosis of more than 80%, and no notable side effects. Our description of this unique case of a patient with MM and isolated CNS relapse after ASCT provides a reference for physicians to provide more appropriate management of these patients. We also reviewed previously reported cases and summarized the outcomes of isolated CNS relapse after ASCT, and discuss the pathogenesis and possible treatment strategies for MM with isolated CNS relapse.